Increased Mesenchymal Stem Cell Response and Decreased Staphylococcus aureus Adhesion on Titania Nanotubes without Pharmaceuticals. (10th November 2015) - Xu, Zhiqiang; Lai, Yingzhen; Wu, Dong; Huang, Wenxiu; Huang, Sijia; Zhou, Lin; Chen, Jiang
Abstract : Titanium (Ti) implants with enhanced biocompatibility and antibacterial property are highly desirable and characterized by improved success rates. In this study, titania nanotubes (TNTs) with various tube diameters were fabricated on Ti surfaces through electrochemical anodization at 10, 30, and 60 V (denoted as NT10, NT30, and NT60, resp.). Ti was also investigated and used as a control. NT10 with a diameter of 30 nm could promote the adhesion and proliferation of bone marrow mesenchymal stem cells (BMSCs) without noticeable differentiation. NT30 with a diameter of 100 nm could support the adhesion and proliferation of BMSCs and induce osteogenesis. NT60 with a diameter of 200 nm demonstrated the best ability to promote cell spreading and osteogenic differentiation; however, it clearly impaired cell adhesion and proliferation. As the tube diameter increased, bacterial adhesion on the TNTs decreased and reached the lowest value on NT60. Therefore, NT30 without pharmaceuticals could be used to increase mesenchymal stem cell response and decrease Staphylococcus aureus adhesion and thus should be further studied for improving the efficacy of Ti-based orthopedic implants.